2019
DOI: 10.1021/acs.jmedchem.8b02009
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Targeted Delivery of 6-Diazo-5-oxo-l-norleucine (DON) Using Substituted Acetylated Lysine Prodrugs

Abstract: 6-Diazo-5-oxo-l-norleucine (DON) is a glutamine antagonist with robust anticancer efficacy; however, its therapeutic potential was hampered by its biodistribution and toxicity to normal tissues, specifically gastrointestinal (GI) tissues. To circumvent DON’s toxicity, we synthesized a series of tumor-targeted DON prodrugs designed to circulate inert in plasma and preferentially activate over DON in tumor. Our best prodrug 6 (isopropyl 2-(6-acetamido-2-(adamantane-1-carboxamido)­hexanamido)-6-diazo-5-oxohexanoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 41 publications
1
53
0
Order By: Relevance
“…Plates were incubated undisturbed at room temperature for 5 hours. Donor and acceptor samples for prodrugs and positive control were quantified by LC/MS-MS as described below (23)(24)(25).…”
Section: Parallel Artificial Membrane Permeation Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Plates were incubated undisturbed at room temperature for 5 hours. Donor and acceptor samples for prodrugs and positive control were quantified by LC/MS-MS as described below (23)(24)(25).…”
Section: Parallel Artificial Membrane Permeation Assaymentioning
confidence: 99%
“…We recently developed targeted GA prodrugs around the parent compound DON in attempt to decrease DON exposure to sites of toxicity (e.g., gut) and preferentially deliver DON to target tissues (e.g., nervous tissues, tumors; refs. [23][24][25]. One such targeted GA termed JHU395 (previously 13d) contains (phenyl(pivaloyloxy)methoxy)carbonyl and isopropyl ester modifications to the amine and carboxylate groups of DON, respectively, which significantly increase its lipophilicity relative to DON (clogP 2.75 vs. À2.5; Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the multitude of targets, DON can be efficacious in the treatment of disease, albeit with potentially strong side effects. Efforts to eliminate side effects are ongoing, including development of prodrugs which exhibit minimal release of DON to gastrointestinal tissues or increased release of DON in tumor cells [106,107]. The wide spectrum of enzymes inhibited by DON leads to tempting speculation of disease treatment when the complex metabolic crosstalk of tumor and stroma is taken into consideration.…”
Section: Therapeuticsmentioning
confidence: 99%
“…One recently described set of molecules was based around 6-diazo-5-oxo-L-norleucine (DON), one of the oldest known inhibitors of GLS [4]. DON is an irreversible substrate-competitive compound, and is generally toxic, with a number of verified targets, and so even though it has excellent efficacy in cell culture it is unsuitable for use in live subjects [4,58]. However, by preparing a series of prodrugs which would be cleaved to DON in cancer cells, researchers from the Johns Hopkins University demonstrated that compounds such as 19 had similar tissue distribution to DON upon injection in mice, but resulted in much lower plasma concentrations of active DON, suggesting it would have reduced off-target effects [59].…”
Section: Anaplerosismentioning
confidence: 99%